Analysis of Interlayer Idle Time as a Temperature Control Technique in Additive Manufacturing of Thick Walls by Means of CMT and CMT Pulse Welding Processes - Silva,Régis Henrique Gonçalves e (2020)
Abstract: Inserted in the scenario of innovations and technological trends of Industry 4.0, this work aims to obtain detailed knowledge on the influence of idle time between layers as thermal control technique for the Wire Arc Additive Manufacturing (WAAM) with two GMAW process variants of high controllability (CMT and CMT Pulse). The problem focuses on the deposition of thick walls, seeking to emulate the challenges of manufacturing big parts with medium geometric complexity, such as propellers and screws, which usually have sections of this thickness. Although works in the area of additive manufacturing point out the use of idle time as a feature to stabilize the thermal gradient, detailed information about the thermal behavior ends up being omitted. Both processes variants used presented high metallic transference stability and low thermal input when compared to the conventional GMAW, being positive differentials for WAAM. In the tests, walls with eight layers were built with ER309LSi steel in which the interlayer idle time varied from 0 to 300 s. It can be concluded that both processes are WAAM compliant, and that although the CMT Pulse has a higher energy input, the temperature control by idle time was able to control the thermal accumulation in the part for both processes.